National capacity assessment report of the Federal Republic of Nigeria : in collaboration with The World Bank - Federal Ministry of Finance; Nigeria, Federal Ministry of Finance; The World Bank (Abuja, Nigeria Federal Ministry of Finance, 2000)
This is a collaborative effort of the Federal Government of Nigeria and the World Bank. It provides a solid basis for the full implementation of the Partnership for Capacity Building (PACT) initiative in Nigeria.
Includes bibliographical references.
opc12/01/17
Loans
Keywords: Economic policy; Economic conditions; Human capital; Nigeria